TEACHERS’ PERCEPTIONS ON THE IMPLEMENTATION OF POP SONGS AND ITS CHALLENGES TO TEACH PRONUNCIATION FOR YOUNG LEARNERS - Ranti Widyastuti; Girindra Saraswati (JELLT (Journal of English Language and Literature Teaching), 2022)
The song is one of the exciting media in verbal communication. Songs as media for teaching pronunciation can help add vocabulary, pronunciation, and grammar contained in the lyrics. This year, teaching and learning have changed online learning into face-to-face learning. Teachers are asked to prepare interesting learning strategies and be able to face challenges. This study aims to determine teachers’ perceptions on the implementation of using pop songs to teach pronunciation and challenge using pop songs to teach pronunciation to young learners. A case study qualitative approach is used in this study through observation and interviews. The research data were collected through observation during pronunciation teaching-learning activities and discussions with three English teachers. The finding shows that using English to teach pronunciation to young learners is very effective, builds self-confidence, and obtains good learning outcomes. In addition, the media used in learning pronunciation does not only use pop songs. Several media are used, including flashcards, drilling, audio, and video. However, the English song of those media still has advantages and disadvantages. The benefits of it include that students are easier to understand, enjoy more, create a pleasant atmosphere, and are easier to remember. Then, the factor becomes obstacles and weaknesses regarding minimal sources, incorrect pronunciation, and unclear writing. In addition, teachers’ perceptions of implementing pop songs to teach pronunciation are positive.